ICF syndrome with variable expression in sibs. Issue 5 (May 1993) - Gimelli, G; Varone, P; Pezzolo, A; Lerone, M; Pistoia, V
Abstract : We describe a new familial case of ICF syndrome (immunodeficiency, centromeric instability, facial anomalies) in a woman of 29 years and in her brother of 30 years. The proband showed mental retardation, facial anomalies, recurrent respiratory infections, combined deficit of IgM and IgE immunoglobulin classes, and paracentromeric heterochromatin instability of chromosomes 1, 9, and 16. The brother had minor signs of the syndrome and had an apparently normal phenotype. Their parents were healthy and non-consanguineous. Chromosome anomalies consisted of homologous and non-homologous associations, chromatid and isochromatid breaks, deletions of whole arms, interchanges in the paracentromeric region, and multibranched configurations of chromosomes 1, 9, and 16. CD bands and fluorescence in situ hybridisation with alphoid DNA sequence probes specific for the centromeres of chromosomes 1 and 16 showed that the centromere was not directly implicated in the formation of multibranched configurations. These cases indicate the autosomal recessive mode of inheritance and the variable expressivity of the ICF syndrome.